2009
DOI: 10.1016/j.apmr.2008.09.559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single-Task Versus Dual-Task Training on Balance Performance in Older Adults: A Double-Blind, Randomized Controlled Trial

Abstract: Objective-To compare the effect of 3 different approaches to balance training on dual-task balance performance in older adults with balance impairment.Design-A double-blind, randomized controlled trial. Setting-University research laboratory.Participants-Older adults (N=23) with balance impairment (mean age, 74.8y). They scored 52 or less on the Berg Balance Scale (BBS), and/or walked with a self-selected gait speed of 1.1m/s or less.Interventions-Participants were randomly assigned to 1 of 3 interventions: si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
363
2
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(415 citation statements)
references
References 36 publications
16
363
2
9
Order By: Relevance
“…Six of the included studies were RTCs [23,29,66,67,80,93]. All six studies, except that of Hall et al [23], were of high quality.…”
Section: Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Six of the included studies were RTCs [23,29,66,67,80,93]. All six studies, except that of Hall et al [23], were of high quality.…”
Section: Selection Criteriamentioning
confidence: 99%
“…Four studies examined walking [66,67,80,104], and two studies combined walking and standing tasks [23,79] to analyse intervention effects on DT performance. -Measurements of motor performance: A variety of different tests and clinical assessments were used to describe motor performance while standing and walking.…”
Section: Classification Of Included Studiesmentioning
confidence: 99%
“…BBS is a tool that makes it possible to quantify balance capacity in tasks such as standing with eyes closed, standing with knees together, and while lifting an object 14) . It scores items from 0 to 4 giving a total ranging from 0 to 56.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that a task-orientated intervention as a complex training method improved both walking distance and walking speed of stroke patients [30]. The observed walking speed improvements after dual-task training were greater than after single-task training when assessed following 4 weeks of balance training in the elderly with disequilibrium [31]. In addition, there was a significant effect on walking speed, average stride length, and cadence after dual-task training [32].…”
Section: Discussionmentioning
confidence: 66%